Film Artifact Optimization Strategy: A Tourist Attraction Case Study of Gamplong Nature Studio - Owie, Anggra Agastyassa; Edy Wibowo; Dimas Erdhinta Pratama Putra (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Film studio design is a process that involves various technical and creative aspects of creating an efficient and flexible production environment. The potential of a film studio setting can vary significantly depending on the size, facilities, location, and infrastructure available. The potential of a film studio setting can vary significantly depending on the size, facilities, location, and infrastructure available. One of the research models used is a descriptive research model. The research model used is a descriptive research model. Data collection used in this study is an interview with Adi Prabowo as the manager of the Alam Gamplong studio, observation to see the studio building directly, and documentation. The results of this study show that the strategy of the Alam Gamplong Studio in making film artifacts as a tourist attraction prioritizes management, innovation, stakeholder collaboration, preservation of film artifacts, promotion of tourist attractions, and solving the challenges being faced.